JURNAL SKRIPSI RANCANG BANGUN SISTEM INFORMASI PELAYANAN ADMINISTRASI BERBASIS WEB DI KELURAHAN SOHO (TEKTO) - Tekto Putra Ayatullah Laheba Tekto; Lestari Retnawati (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2022)
Urban village is a very important government agency, the urban village office itself has a very important role in public administration services. Soho Village is a sub-district in Luwuk District which handles all population data such as applications for making Identity Cards, Applications for making Family Cards, moving certificates and others. In the urban village area, all data is handled manually, such as too many forms which require a large amount of money, if the requirements collected are incomplete. First, residents must come directly to the urban village by bringing all the requirements as needed, but due to the lack of clarity of information obtained, sometimes residents have to return home to complete the missing requirements. The system is made web-based with the PHP programming language and MySQL database. The software development methodology used in the system is the waterfall method. Keywords: Urban Village, Resident, PHP, MySQL, Web, Waterfall